2012
DOI: 10.1038/nrn3406
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of α-synuclein: from structure and toxicity to therapeutic target

Abstract: Disorders characterized by α-synuclein (α-syn) accumulation, Lewy body formation and parkinsonism (and in some cases dementia) are collectively known as Lewy body diseases. The molecular mechanism(s) through which α-syn abnormally accumulates and contributes to neurodegeneration in these disorders remains unknown. Here, we provide an overview of current knowledge and prevailing hypotheses regarding the conformational, oligomerization and aggregation states of α-syn and their role in regulating α-syn function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
1,442
0
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,424 publications
(1,480 citation statements)
references
References 129 publications
(176 reference statements)
15
1,442
0
23
Order By: Relevance
“…Most recent evidence suggests that oligomers and probably also protofibrils are toxic to neurons by disrupting synaptic function, membrane permeability, calcium homeostasis, gene transcription, mitochondrial activity, autophagy, and/or endosomal transport [18][19][20][21]. Moreover, recent studies have shown that propagation and seeding of Aβ, tau, and α-syn in a prion-like manner might also contribute to neurodegeneration [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Most recent evidence suggests that oligomers and probably also protofibrils are toxic to neurons by disrupting synaptic function, membrane permeability, calcium homeostasis, gene transcription, mitochondrial activity, autophagy, and/or endosomal transport [18][19][20][21]. Moreover, recent studies have shown that propagation and seeding of Aβ, tau, and α-syn in a prion-like manner might also contribute to neurodegeneration [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…α-Synuclein (α-syn) instigates both sporadic and idiopathic Parkinson's disease (PD) by various modes of action [1] and is the major component of intracellular Lewy bodies and Lewy neurites in the brain [2]. The three rare missense mutations of α-syn (A30P, A53T and E46K), copy number variants and two probable substitutions (H50Q and G51D) are associated with familial PD, indicating a central role for this protein [3].…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and associated mode of toxicity displayed by alternative types of α-syn oligomers are largely dependent on the environmental conditions under which they have been prepared [6][7][8][9][10][11]. Numerous in vitro and in vivo studies on α-syn oligomers have demonstrated that a toxic gain-offunction occurs in the disease state via two main mechanisms: (i) Ca 2 + imbalances caused by the formation of pore-like complexes within lipid membranes, and (ii) transmembrane seeding that then results in intracellular aggregation [1]. α-Syn is expressed as an intracellular protein but has been shown to be directly secreted or released as a result of neuronal death or stress conditions into the extracellular space [12].…”
Section: Introductionmentioning
confidence: 99%
“…The processes of α‐synuclein oligomerization and fibril growth play central roles in the pathogenesis of Parkinson's disease (Lashuel et al . 2013) and are influenced by monoubiquitylation. Monoubiquitylation by the E3 ligase SIAH (at K10, K12, K21, K23, K34, K43 or K96) promotes α‐synuclein aggregation (Rott et al .…”
Section: Regulation Of Neuronal Proteins By Monoubiquitylationmentioning
confidence: 99%